When Philanthropy Funds Government: An Exploration of Democratic Public Values. (4th March 2022) - Fenley, Vanessa M.; Bodenhamer, Nina
Abstract : Using philanthropy to fund public services can provide capacity for government, but these arrangements raise questions regarding the impact to democratic public values. This research explores how democratic public values are expressed in a philanthropic program managed by the local city government in Fort Collins, Colorado. Data indicate that City staff developed program strategies that reflect democratic public values, including expanding opportunities for participation by community members and considering how funds can be used to equitably serve the community. However, incorporating these strategies into the program model did not happened automatically. It has required rethinking the program's purpose, considering its role in creating public value beyond providing increased financial capacity.